Accessibility and Amenity Challenges in the Development of Ecotourism Attractions: An Evaluative Study of Curug Kedung Kudhu. - Sagita, Novieta Maya; Mistriani, Nina (Institute of Computer Science (IOCS), 2025)
This study aims to evaluatively examine the challenges of accessibility and amenities in the development of Curug Kedung Kudhu ecotourism attraction. Through a qualitative interpretive approach based on constructivist epistemological principles, the study seeks to uncover the complexities of obstacles encountered in transforming Curug Kedung Kudhu into an accessible and comfortable nature tourism destination for visitors. Primary data were collected through semi-structured interviews with purposively selected participants, analysis of institutional records, and triangulation of various data sources to ensure the research's credibility. The findings reveal three main themes representing challenges in accessibility and amenities: (1) inadequate infrastructure accessibility; (2) limited tourist amenities; and (3) suboptimal destination governance. This research highlights the complexity of infrastructure, governance, and amenity barriers that need to be addressed holistically and collaboratively. The resulting policy recommendations emphasize the importance of multi-stakeholder collaboration, local community empowerment, and sustainable destination planning and management. By adopting a comprehensive community-based ecotourism approach, Curug Kedung Kudhu has the potential to become a model for the development of an inclusive and sustainable nature tourism destination that provides optimal benefits for local communities and environmental conservation.